PH‐receptive chlorhexidine‐loaded poly‐L‐glycolic acid platform delivery approach to stabilize adhesive‐orthodontic interface. Issue 10 (10th August 2021) - Kamran, Muhammad Abdullah; A Alnazeh, Abdullah; Hameed, Mohammad Shahul; Yassin, Syed M.; Mannakandath, Master Luqman; Alshahrani, Ibrahim
Abstract: This study aimed to synthesize and characterize chlorhexidine (CHX)‐loaded poly‐L‐glycolic acid (PLGA) nanoparticles and to investigate the in vitro drug release in different pH conditions, antibacterial, cytotoxicity activity, and mechanical properties of CHX‐loaded PLGA‐modified Transbond XT adhesive at tooth‐bracket interface. PLGA nanoparticles with and without CHX were synthesized using emulsion diffusion method and characterized for morphology and chemical structure using transmission electron microscopy and Raman analysis. CHX‐loaded PLGA nanoparticles in Transbond XT orthodontic adhesive were prepared using two different concentrations of the nanoparticles (2.5 and 5 wt%) and characterized for degree of conversion (DC) using DC, antimicrobial MTT assay, and cytotoxicity testing. Bonded specimens were tested for shear bond strength (SBS) and adhesive remnant index (ARI) at the tooth‐bracket interface. The synthesized PLGA nanoparticles averaged between 60 and 80 nm in size. After loading CHX inside PLGA nanoparticles, the morphology of the PLGA nanoparticles was changed considerably into irregular shaped structures. Bracket samples treated with 5 wt% CHX‐loaded PLGA‐modified adhesive demonstrated the least mean DC scores. A 5 wt% CHX‐loaded PLGA‐modified adhesive specimens showed more profound antibacterial activity against Streptococcus mutans . The least mean SBS values were exhibited by 5 wt% CHX‐loaded PLGA‐modified adhesive samples, while a statistically significant difference was observed in the mean ARI values among all study groups at all‐time points ( p = 0.018). A pH‐sensitive CHX release response was observed when loaded in PLGA nanoparticles. The formulated drug‐loaded nanocarrier exhibited remarkable physicochemical, spectral, and biological features.